2005
DOI: 10.1590/s1415-52732005000600006
|View full text |Cite
|
Sign up to set email alerts
|

Regulação da expressão gênica das UCP2 e UCP3 pela restrição energética,jejum e exercício físico

Abstract: O tecido adiposo marrom, onde se localiza a proteína desacopladora 1 (UCP1 - uncoupling protein 1), é um tecido termogênico presente somente nos pequenos mamíferos e neonatos, com função de manter temperatura e peso corporal estáveis quando da exposição ao frio ou consumo de dietas hipercalóricas. Como a UCP1 está localizada exclusivamente no tecido adiposo marrom, tecido pouco expressado em adultos, os estudos dão ênfase às proteínas desacopladoras 2 e 3 (UCP2 e UCP3), proteínas homólogas à UCP1, expressas em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
2
0
3
Order By: Relevance
“…The uncoupling of respiration and the dissipation of heat are important keys to energy balance [21]. When a stimulus occurs to a UCP, energy is not taken to the phosphorylation of the ADP, and heat is generated [26,27]. Also, UCPs are involved in other cellular processes such as mitochondrial free radical production [28].…”
Section: Discussionmentioning
confidence: 99%
“…The uncoupling of respiration and the dissipation of heat are important keys to energy balance [21]. When a stimulus occurs to a UCP, energy is not taken to the phosphorylation of the ADP, and heat is generated [26,27]. Also, UCPs are involved in other cellular processes such as mitochondrial free radical production [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CLA has shown to increase adiponectin, an anti-inflammatory hormone that lowers gluconeogenesis, and reduces circulating levels of leptin [ 77 , 90 ]; however, one study revealed that leptin and adiponectin levels were unaffected by CLA supplementation [ 91 ]. Another plausible mechanism by which CLA modulates body composition and weight loss is related to PPARs, especially PPARγ, as CLA can reduce the expression of lipogenesis-related genes and decrease body fat by inhibiting PPARγ [ 92 ].…”
Section: Cla Effects On Body Compositionmentioning
confidence: 99%
“…O jejum é caracterizado pela supressão da ingestão de alimentos por um período prolongado 1 . Vários profissionais de saúde assim como o senso comum, defendem que praticar exercícios físicos em jejum pode potencializar os efeitos da prática regular de atividades físicas com objetivo de emagrecimento 2 .…”
Section: Introductionunclassified